Koreografi Tari Tobo Baombai di Nagari Sijunjung Kecamatan Sijunjung Kabupaten Sijunjung - Jupriyanto Jupriyanto; Herlinda Mansyur (SENDRATASIK UNP, 2023)
This study aims to reveal and describe the choreography process of Tobo Baombai Dance in Nagari Sijunjung, Sijunjung District, Sijunjung Regency. This type of research is qualitative with a descriptive method. This research instrument is the researcher himself and is assisted by supporting instruments such as stationery and cameras. The types of data in this study are primary data and secondary data. Data collection techniques use literature studies, observations, interviews and documentation. The steps of analyzing data are data collection, data reduction, data presentation and drawing conclusions. The results showed that Tobo Baombai Dance is a traditional dance that has simple movements and Tobo Baombai Dance consists of aspects of form and content. The shape aspect consists of motion, floor design, top design, group composition, dancers, costumes, music and props. The content aspect consists of ideas and atmospheres. The idea of the Tobo Baombai dance is a form of activity of the Nagari Sijunjung community in absorbing their rice fields, while the atmosphere arises from the spirit and never give up, for the activities carried out, namely plowing the fields.